Factor VIII levels during the course of acute hepatitis in a haemophiliac. Issue 12 (December 1975) - Gazzard, B G; Clark, R; Flute, P T; Williams, R
Abstract : A 51-year-old patient with haemophilia since childhood (usual factor VIII level 14%) developed acute viral hepatitis type B two months after an operation which had been covered by cryoprecipitate. The course of the hepatitis following admission was severe with encephalopathy and ascites. Evidence of intravascular coagulation with an increased radioactive fibrinogen turnover was also present. The factor VIII level measured by a one-stage clotting factor assay rose rapidly to 200% of normal and remained at this level for two weeks, and factor-VIII-related antigen as measured by electroimmunoassay also became greatly elevated (900% of normal). The possible mechanisms underlying those surprising changes are discussed.